Real-time cost-tracking software tool via life cycle cost analysis : methodological implementation of lcca framed within integrated logistic support (2024)
In this document, a user-friendly software tool for life cycle cost analysis (LCCA) was developed using Python alongside a task model approach. The tool employs a graphical representation of cumulative costs, encompassing acquisition, operational, maintenance, and disposal costs. The software was employed for cost-benefit analysis and the generation of real-time indicators for COTECMAR. The objective of the analysis was to identify the most cost-effective investment and to provide support for asset-management decision-making. LCCA is a daunting mathematical computation that is contemplated and characterized by engineering economic standards such as ISO 15686 and NATO TR SAS 054. The developed products include a comprehensive life-cycle cost (LCCA) methods implementation, a bespoke software tool, and a project development report. The project team acquired advanced expertise in the fields of cost analysis, software development, naval industry standards, and logistic support process integration. This comprehensive approach is designed to enhance the reliability and operational efficiency of systems and equipment in the industry.